Vigilance on New-Onset Atherosclerosis Following SARS-CoV-2 Infection - Liu, Ya; Zhang, Hai-Gang (Frontiers in Medicine, 2021)
The pandemic of coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, has become a global challenge to public health. While its typical clinical manifestations are respiratory disorders, emerging evidence of cardiovascular complications indicates the adverse interaction between SARS-CoV-2 infection and cardiovascular outcomes. Given that viral infection has emerged as an additional risk factor for atherosclerosis, in this paper, we attempt to clarify the susceptibility to new-onset atherosclerosis in individuals infected with SARS-CoV-2. Mechanistically, serving as functional receptors for SARS-CoV-2, angiotensin-converting enzyme 2 (ACE2) mediates SARS-CoV-2 infection of endothelial cells (ECs) directly, leading to endothelial dysfunction and dysregulation of the renin-angiotensin system (RAS). In addition, high expression of CD147, an alternative receptor, and activation of the NLRP3 inflammasome may also contribute to atherosclerosis in the context of COVID-19. More importantly, SARS-CoV-2 attacks the immune system, which results in excessive inflammation and perpetuates a vicious cycle of deteriorated endothelial dysfunction that further promotes inflammation. The alterations in the blood lipid profile induced by COVID-19 should not be ignored in assessing the predisposition towards atherosclerosis in victims of COVID-19. A better understanding of the underlying mechanisms of SARS-CoV-2 infection and the long-term monitoring of inflammatory factors and endothelial function should be considered in the follow-up of patients who have recovered from COVID-19 for early detection and prevention of atherosclerosis.